Is the determination of bone turnover markers and vitamin D useful in the diagnosis of degeneration spine disease? - Liczner, Grzegorz; Wiciński , Michał; Cadelski, Karol; Malinowski, Bartosz (Journal of Education, Health and Sport, 2021)
Abstract: Degenerative disease of the lumbar spine is one of the most common diseases of the human musculoskeletal system and a significant public health problem. The main manifestation of degenerative spine disease is back pain, which in most cases is treated symptomatically rather than causally. The diagnosis of degenerative spine disease has been previously based on medical history and diagnostic imaging. Recently, much attention has been devoted to the biochemical indicators of bone and cartilage metabolism, which are well understood among patients with osteoporosis. Bone turnover markers indicate the metabolic activity of bone and cartilage. They occur in blood serum, urine, and synovial fluid in the form of collagen-derived proteins or enzymes, involved in the formation or resorption of bone and cartilage tissue. The study below was aimed at assessing the usefulness of determining the markers of bone turnover and cartilage damage in the blood serum of people with degenerative disease of the lumbar spine diagnosed by MRI. The biochemical diagnostics included the measurement of inflammatory parameters. The results show that the degenerative disease of the spine is local, accompanied by inflammation, and vitamin D deficiency is among the factors leading to its development.